The Effect of Profitability, Growth Opportunities and Liquidity on Company Capital Structure on the Indonesia Stock Exchange: Pengaruh Profitabilitas, Peluang Pertumbuhan dan Likuiditas terhadap Struktur Modal Perusahaan di Bursa Efek Indonesia - Elta Aprilia; Yuliadi (International Journal of Management and Business (IJMB), 2020)
This study discusses to examine the effect of profitability, growth opportunities and liquidity on the capital structure of companies on the Indonesia Stock Exchange for the period 2015 to 2019. This study uses secondary data with quantitative methods. The samples used were 8 companies from a total of 13 automotive sub sector companies and components obtained from the Indonesia Stock Exchange using a purposive sampling method. Using the method of multiple linear regression analysis, hypothesis testing (t test, f test and determination test) which tests with the classic assumption test and descriptive statistics. The results obtained are not significant profitability on the Capital Structure assessed by the probability value in the t-statistic test shows a value of 0.877 where the value is greater than the significance value of 0.05. Growth opportunities are not significant to the Capital Structure, the calculation results obtained from the t-statistic test show a probability value of 0.477 which means a value greater than 0.05. Liquidity has a significant effect on capital structure, the results of calculations obtained from the t-statistic test show a probability value of 0,000, which means a value less than 0.05 capital in companies on the Indonesia Stock Exchange.